Vocabularies in the Bau and Soloira dialects - Carew, Walter S.
Vocabularies in English with equivalent words in the Bau and Soloira dialects used on Viti Levu, Fiji, compiled by Carew.
Collection material in English, with Bau dialect, and Soloira dialect.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Viti Levu (Fiji); Language and languages